Development of An Inclusive Curriculum Based on Islam and Technology at Madrasah Aliyah - Abidin, Zaenal; A’yun, Fatihatul; Isnandar, Arvin (Kirana Publisher (KNPub), 2025)
The ever-evolving digital era requires Madrasah Aliyah to provide an inclusive education that is able to integrate Islamic values and technology in support of multiculturalism. In practice, ideal conditions are often not achieved due to limited resources and a lack of synergy between Islamic principles, technological innovation, and cultural diversity. This inequality gave birth to two main research focuses, namely the exploration of how to combine Islamic values and technology to support multiculturalism and the identification of challenges and strategies for the implementation of an inclusive curriculum based on Islam and technology. This research was carried out with a qualitative approach through the library research method, where data was obtained from literature studies and digital documentation and then analyzed thematically. The results of the study reveal that the integration of Islamic values and technology can be optimized through the framework of multiculturalism in the style of James A. Banks and Jerome Bruner's theory of constructivism. The main challenges lie in the limitations of technological infrastructure and resistance to change, while the strategies include teacher training, strengthening multi-stakeholder collaboration, and developing technology-based learning modules. In conclusion, the integration of Islamic values and technology can be realized through a holistic approach that accommodates multiculturalism, while the implementation of an inclusive curriculum requires synergy between madrasah capacity, technological innovation, and adaptation to challenges. Recommendations are given to improve teacher competence and design a curriculum model that is more responsive to multicultural needs.